Dinamika Perubahan Komoditas Pertanian dan Implikasinya terhadap Kondisi Tanah di Desa Lantang Tallang, Kabupaten Luwu Utara - Dian Hendrayanti; Nisrina Nur Azizah; Amanda Syahda; Anggun Rizka Amini; Yuni Riyanti (Yayasan Literasi Sains Indonesia, 2026)
Land-use transformation is one of the major consequences of transmigration area development in Indonesia. Desa Lantang Tallang, Masamba District, North Luwu Regency, has experienced significant changes in its agricultural system since the arrival of transmigrants in 2013. This study aims to analyze the dynamics of agricultural commodity changes over the past decade and examine their implications for soil conditions and land management in plantation-based farming systems. The research employed a survey approach using field observations, semi-structured interviews, and secondary village data. Data were analyzed using descriptive-comparative methods and Location Quotient analysis to identify leading commodities. The results indicate a transition from food-crop-based farming toward plantation dominance, particularly oil palm, which shows the highest Location Quotient value. While this transition contributes to increased household income, it also intensifies the use of chemical fertilizers and dependence on external inputs, potentially leading to long-term soil degradation. These findings demonstrate that commodity transformation in transmigration areas simultaneously reshapes rural economic structures and generates socio-ecological consequences, highlighting the need for sustainable land management strategies.